STEAM-Based Science and Social Science Modules Integrated with Tri N to Improve Creativity of Elementary School Students - Armi, Yustina; Pardimin; Nisa, Ana Fitrotun (International Journal of Elementary Education, 2025)
Creativity is a skill that must be possessed the 21st century. The low level of creativity possessed by elementary school students makes it necessary to develop learning resources that can improve student creativity. This study aims to innovating the natural and sciences module with characteristics based in STEAM integrated with Tri N that feasible and effective to improve the creativity of elementary school students. The method used in the study is ADDIE, namely: analysis, design, development, implementation, evaluation. Data collection techniques include interviews, questionnaires, observation and documentation. The data analysis technique in this research uses qualitative and quantitative data analysis techniques. The research subjects of this research were fifth grade elementary school students. Results of the study showed that generated Natural and Social Sciences Module based on STEAM integrated with Tri N that feasible and effective to improve the creativity of elementary school students. Results of module's feasibility obtained the criteria for a module that is feasible for use in learning process. Material experts gave a score of 97 to the product with very feasible criteria. Elementary school learning resource experts gave a score of 98.26 to the product with very feasible criteria. The module developed has also proven effective in increasing elementary school students' creativity as evidenced by the increase in observation scores from 38.33 to 68.33 in limited trials, and increasing from 37.23 to 81.38 in extensive trials.